Plasma acylcarnitine concentrations reflect the acylcarnitine profile in cardiac tissues - Makrecka-Kuka, Marina; Sevostjanovs, Eduards; Vilks, Karlis; Volska, Kristine; Antone, Unigunde; Kuka, Janis; Makarova, Elina; Pugovics, Osvalds; Dambrova, Maija; Liepinsh, Edgars (Scientific reports, 2017)
Increased plasma concentrations of acylcarnitines (ACs) are suggested as a marker of metabolism disorders. The aim of the present study was to clarify which tissues are responsible for changes in the AC pool in plasma. The concentrations of medium- and long-chain ACs were changing during the fed-fast cycle in rat heart, muscles and liver. After 60 min running exercise, AC content was increased in fasted mice muscles, but not in plasma or heart. After glucose bolus administration in fasted rats, the AC concentrations in plasma decreased after 30 min but then began to increase, while in the muscles and liver, the contents of medium- and long-chain ACs were unchanged or even increased. Only the heart showed a decrease in medium- and long-chain AC contents that was similar to that observed in plasma. In isolated rat heart, but not isolated-contracting mice muscles, the significant efflux of medium- and long-chain ACs was observed. The efflux was reduced by 40% after the addition of glucose and insulin to the perfusion solution. Overall, these results indicate that during fed-fast cycle shifting the heart determines the medium- and long-chain AC profile in plasma, due to a rapid response to the availability of circulating energy substrates.